Engaging students with game-based learning: applying Quizziz and Quizwhizzer in teaching economics / Norsilawati Mohd Hassan ... [et al.] - Mohd Hassan, Norsilawati; Nik Hassan, Nik Suriati; Ab Rani, Nor Zuriati Amani; Zahari, Nor Sabrina; Husin, Suraya (2023)
Modern educational practices include a wide range of innovative techniques that use technology, interactive learning, and individualized instruction to enhance the learning process. The use of interactive games that include educational content is an effective tool for engaging students. It makes learning entertaining while improving motivation, critical thinking, and problem-solving abilities. A dynamic and engaging learning environment can be produced by utilizing several game techniques, such as rewards, competition, and teamwork. Quizizz and Quizwhizzer are the two online assessment tools that have been applied to this innovation to encourage students’ participation and commitment in the classroom while learning economics, r digitally or physically. Quizizz and Quizwhizzer are engaging educational game tools that can turn materials or questions into interactive games that can be used to build quizzes. These two web tools are also user-friendly and accessible from various devices with an internet connection. It also allows students to participate from different locations and devices. The unique features, such as self-paced learning, customization, points, and a leaderboard, have motivated students to actively participate in the quizzes. The findings show that more than 80% of respondents agree that using Quizizz and Quizwhizzer can help to create an interactive learning environment, increase engagement for teaching and learning purposes, and encourage visual participation in teaching and learning activities. Therefore, implementing game-based learning in the classroom is advised to increase student engagement and finally enhance students' results in learning economics in parallel with the Sustainable Development Goal (SDG) to achieve quality education.